Methodological Framework of Conduct for Integrated Psychological and Psychiatric Examinations in Disputes about the Right to Raise Children - N. K. Kharitonova; F. S. Safuanov; N. V. Vostroknutov; O. A. Rusakovskaya (Теория и практика судебной экспертизы)
.